Modern Views on the Etiology and Pathogenesis of Chronic Tonsillitis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, inflammatory diseases of the upper respiratory tract are extremely important. The cause of the development of chronic tonsillitis is a change in the reactivity of the body to microbes. Various complications of chronic tonsillitis lead not only to the fact that ENT doctors, but also other healthcare industries are fixated on this problem. Currently, the treatment of chronic tonsillitis remains an unresolved problem until the end.